Mitohormesis, UPR(mt), and the complexity of mitochondrial DNA landscapes in cancer - Kenny, Timothy C. (Cancer Res, 2019)
The discovery of the Warburg effect - the preference of cancer cells to generate ATP via glycolysis rather than oxidative phosphorylation has fostered the misconception that cancer cells become independent of the electron transport chain (ETC) for survival. This is inconsistent with the need of ETC function for the generation of pyrimidines. Along with this misconception, a large body of literature has reported numerous mutations in mitochondrial DNA (mtDNA) further fueling the notion of non-functional ETC in cancer cells. More recent findings, however, suggest that cancers maintain oxidative phosphorylation capacity and that the role of mtDNA mutations in cancer is likely far more nuanced in light of the remarkable complexity of mitochondrial genetics. This review aims at describing the various model systems that were developed to dissect the role of mtDNA in cancer, including cybrids, and more recently mitochondria-nuclear exchange (MNX) and conplastic mice. Further, we put forward the notion of mtDNA landscapes, where the surrounding non-synonymous mutations and variants can enhance or repress the biological effect of specific mtDNA mutations. Notably, we review recent studies describing the ability of some mtDNA landscapes to activate the mitochondrial unfolded protein response (UPRmt), but not others. Further, the role of the UPRmt in maintaining cancer cells in the mitohormetic zone to provide selective adaptation to stress is discussed. Among the genes activated by the UPRmt, we suggest that the dismutases SOD2 and SOD1 may play key roles in the establishment of the mitohormetic zone. Finally, we propose that using a UPRmt nuclear gene expression signature may be a more reliable readout than mtDNA landscapes given their diversity and complexity.